2019
DOI: 10.1111/pala.12459
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic factors driving the diversification dynamics of Crocodylia

Abstract: Species diversity patterns are governed by complex interactions among biotic and abiotic factors over time and space, but are essentially the result of the diversification dynamics (differential speciation and extinction rates) over the long‐term evolutionary history of a clade. Previous studies have suggested that temporal variation in global temperature drove long‐term diversity changes in Crocodylia, a monophyletic group of large ectothermic organisms. We use a large database of crocodylian fossil occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 114 publications
0
25
0
Order By: Relevance
“…In the geologic time scale, macroevolutionary analysis of body size in extinct crocodyliforms can illuminate the rate and mode of the evolution and factors responsible for the long-term disparity patterns ( Godoy et al. 2019 ; Gearty and Payne 2020 ; Solórzano et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the geologic time scale, macroevolutionary analysis of body size in extinct crocodyliforms can illuminate the rate and mode of the evolution and factors responsible for the long-term disparity patterns ( Godoy et al. 2019 ; Gearty and Payne 2020 ; Solórzano et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the diversification and decline phases, abiotic forcing is the primary factor controlling the loss and accumulation of species [55]. Further studies have similarly suggested that diversification rate is limited by within-clade diversity (and, by extension, intra-clade biotic interactions), while extinction rate may, most often, be set by abiotic factors [21,42,57,58].…”
Section: Biotic Interactions As Drivers Of Macroevolutionmentioning
confidence: 99%
“…Inferring the importance of biotic interactions on the basis of statistical rejection of abiotic factors is the most common approach employed by recent publications [24,42,46,58,59]. There are potential limitations to these modeling approaches (Table 1), and continued characterization of their statistical behavior will be important to assess validity.…”
Section: Biotic Interactions As Drivers Of Macroevolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…When both extinct and extant crocodyliform taxa are examined together, the clade displays a bimodal diversity distribution that roughly corresponds to the δ 18 O curve for the Cenozoic ( Markwick, 1998 ) and reflect the bimodal changes in global temperature during this time ( Mannion et al, 2015 ). Other factors may be driving this pattern ( Jouve et al, 2017 ; Solórzano et al, 2019 ; Celis, Narváez & Ortega, 2020 ), but climate is nonetheless viewed as a major factor influencing crocodyliform diversity patterns over time.…”
Section: Introductionmentioning
confidence: 99%